Late blight disease of tomato: A serious problem for Indian tomato farmers - Singh, Raghuveer (Indian Horticulture, 2026)
Late blight is a devastating disease caused by Phytophthora infestans. It spreads rapidly in cool, humid weather and can destroy tomato crops, leading to significant losses. Symptoms include water-soaked spots on leaves, dark patches, greasy-looking stems, and sunken lesions on fruits. In areas with high rainfall, farmers should grow the variety Arka Abhed F1 or follow a six-canopy spray schedule using copper oxychloride (2.5 g per liter of water), along with soil mulching, for susceptible tomato hybrids and varieties.